The Roaring Lion: Critical Musicology, the Aesthetic Experience, and the Music Department - Gramit, David (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1998)
This paper argues that a number of recent responses within North American musicology to critical scholarship that has challenged disciplinary conventions have in common a deep loyalty to the aesthetic experience of music as a supreme value. The vigour with which this value is defended has close parallels in religion, and such defences have indeed sometimes resorted to explicitly religious terminology. The institutional situation of North American musicology in university music departments dominated by Western classical music instruction strengthens this ideology, which continues to resist socially oriented study of music.